Study of plaster finishes on San Pedro de los Francos church at Calatayud - R. Bustamante; Mª I Sánchez de Rojas (Materiales de Construccion, 2007)
This study of the plaster finishes on San Pedro de los Francos Church at Calatayud revealed, firstly, the stratigraphic sequence based on the interpretation of the bonding interfaces; and secondly, the evolution of placement techniques from mudéjar style textured and painted false stonework (15th century) to the smooth plastering and paint typical of later phases. Finally, scanning electron microscope (SEM), energy dispersive X-ray microanalysis (EDX) and X-ray diffraction (XRD) studies showed that gypsum and anhydrite are the main components of both binder and aggregate in these mortars. In other words, they constitute traditional multiphase plasters whose coarser particles or aggregate were a byproduct of the artisanal manufacturing process.